The International Encyclopedia of Health Communication 2022
DOI: 10.1002/9781119678816.iehc0625
|View full text |Cite
|
Sign up to set email alerts
|

Entertainment‐Education (Effects)

Abstract: Entertainment‐education (EE) was first defined as a health communication strategy that used media designed to increase individual knowledge, change attitudes, and shift behavior. Early EE programs focused on family planning and other health issues and utilized a long‐running narrative format on radio and television. Early EE effects research focused on individual‐level data and outcomes, such as knowledge and behavior, to understand if EE worked. Over time, the definition of EE has evolved to reflect a changin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The art and science of storytelling in recent decades have taught us that, when told well, stories are powerful. They can not only change people's minds and actions but also fight social ills and save millions of lives (e.g., Green et al, 2002;Kreuter et al, 2007;Riley et al, 2022;Singhal & Rogers, 1999;Singhal et al, 2013). This might just be the secret to the survival of the human species and all life on Earth.…”
Section: Hua Wang and Emily Corenmentioning
confidence: 99%
See 1 more Smart Citation
“…The art and science of storytelling in recent decades have taught us that, when told well, stories are powerful. They can not only change people's minds and actions but also fight social ills and save millions of lives (e.g., Green et al, 2002;Kreuter et al, 2007;Riley et al, 2022;Singhal & Rogers, 1999;Singhal et al, 2013). This might just be the secret to the survival of the human species and all life on Earth.…”
Section: Hua Wang and Emily Corenmentioning
confidence: 99%
“…In the span of over 50 years, the idea of intentionally combining entertainment with education for health promotion and behavior change, known as entertainmenteducation or edutainment, has evolved into a field of research and practice around the globe, making a significant impact at the individual, interpersonal, community, and societal levels (Frank & Falzone, 2021;Riley et al, 2022;Singhal et al, 2013;Storey & Sood, 2013;Wang & Singhal, 2021a). In its early years, from the 1970s to the early 2000s, practitioners mainly worked with government agencies, nongovernmental organizations, and creative professionals in developing countries to create prosocial radio and television serial dramas (Singhal et al, 2004;Singhal & Rogers, 1999).…”
Section: Entertainment-education For Social and Behavior Changementioning
confidence: 99%
“…Research in neuroscience, social sciences, and humanities has shown that information presented in a narrative format is easier to attract and sustain attention and creates shortcuts to facilitate comprehension and recall because it is more accessible and engaging (Gottschall, 2012;Polkinghorne, 1988;Schneider-Mayerson et al, 2023). Powerful stories can change people's knowledge, attitudes, practices, and social norms (Bálint & Bilandzic, 2017;Bilandzic & Kinnebrock, 2009;Green et al, 2002;Murphy et al, 2015;Riley et al, 2022;Singhal & Rogers, 1999;Singhal et al, 2013). We rely on storytelling to organize information, generate meaning, and make sense of ourselves in the world and how we are related to each other (Gottschall, 2012;Polkinghorne, 1988).…”
Section: Storytelling As a Climate Change Communication And Action St...mentioning
confidence: 99%
“…Decades of research (e.g., Green et al, 2002Green et al, , 2019Frank & Falzone, 2021;Riley et al, 2022;Singhal et al, 2004Singhal et al, , 2013Singhal & Rogers, 1999;Storey & Sood, 2013) have shown that:…”
Section: Power Of Storytelling In Popular Entertainment For Social An...mentioning
confidence: 99%